Analisis Model Bisnis sebagai Upaya untuk Mencapai Stabilitas dan Keterjangkauan Harga Komoditas Strategis di Provinsi Papua Selatan - Syukron, Nurkholis (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
This study aims to analyze business models that can be applied to achieve stability and affordability of strategic commodity prices in Papua Selatan Province. The region faces various challenges such as geographical factors, limited infrastructure, and long supply chains, all of which contribute to commodity price fluctuations. The research employs a mixed-methods approach, including surveys, in-depth interviews, and secondary data analysis to identify effective business models. The results show that integrated business approaches, partnerships with local communities, and the utilization of digital technology can significantly reduce operational costs and improve distribution efficiency. Integrated farming models and the use of blockchain technology have proven effective in reducing dependence on intermediaries and enhancing supply chain transparency. Additionally, government and private sector partnership programs in infrastructure development also show great potential in reducing logistics costs. By implementing more efficient and integrated business models, it is expected that the prices of strategic commodities in Papua Selatan can be kept stable and affordable, thus improving community welfare. This study suggests that government support in the form of subsidies and incentives, as well as enhancements in economic and technological literacy, are crucial for the successful implementation of these business models.